Assessing the noise impact on residential façades on the Maceió-AL Waterfront (Research, Society and Development, 2022)
As a result of the disorderly growth of cities, problems arise in vehicular traffic and in the uses and occupations of buildings, factors that intensify the urban noise. The Avenida Silvio Carlos Viana is the target of complaints registered by the Secretariat of Territorial Development - SEDET, being the commercial establishments, bars and restaurants the major causes of noise discomfort. The aim of this work is to evaluate the implementation of leisure activities and the noise impact on the residential areas façades in the clipping of the Ponta Verde district in Maceió-AL, Brasil. From measurements of sound pressure levels, Leq (A), on Sundays where the area is off-limits for recreational use. These measured data will be implemented using the software CadnaA, to evaluate the local acoustic scenario and the vertical buildings by the sea. Thus, it is noticeable that the population is inserted in buildings with low acoustic performance, thus being exposed to high levels of residual noise, and may suffer damage not only to hearing health, but also causing psychological and cardiac damage over time.